An atypical presentation of Todd’s Paralysis - Rashad Brahim; Narine Mack; Darren Gopaul; Jessica Rampersad (Caribbean Medical Journal)
Stroke mimics (SM) such as Todd’s paralysis pose a major diagnostic challenge and may be difficult to distinguish from Transient Ischemic Attacks (TIA). The aim of this case presentation was to highlight a case where the presentation made it difficult to ascertain the true cause of patients' quadriplegia.